Idiopathic basal ganglia calcification‐associated PDGFRB mutations impair the receptor signalling. Issue 1 (8th October 2014) - Arts, Florence A.; Velghe, Amélie I.; Stevens, Monique; Renauld, Jean‐Christophe; Essaghir, Ahmed; Demoulin, Jean‐Baptiste
Abstract Platelet‐derived growth factors (PDGF) bind to two related receptor tyrosine kinases, which are encoded by the PDGFRA and PDGFRB genes. Recently, heterozygous PDGFRB mutations have been described in patients diagnosed with idiopathic basal ganglia calcification (IBGC or Fahr disease), a rare inherited neurological disorder. The goal of the present study was to determine whether these mutations had a positive or negative impact on the PDGFRB activity. We first showed that the E1071V mutant behaved like wild‐type PDGFRB and may represent a polymorphism unrelated to IBGC. In contrast, the L658P mutant had no kinase activity and failed to activate any of the pathways normally stimulated by PDGF. The R987W mutant activated Akt and MAP kinases but did not induce the phosphorylation of signal transducer and activator of transcription 3 (STAT3) after PDGF stimulation. Phosphorylation of phospholipase Cγ was also decreased. Finally, we showed that the R987W mutant was more rapidly degraded upon PDGF binding compared to wild‐type PDGFRB. In conclusion, PDGFRB mutations associated with IBGC impair the receptor signalling. PDGFRB loss of function in IBGC is consistent with recently described inactivating mutations in the PDGF‐B ligand. These results raise concerns about the long‐term safety of PDGF receptor inhibition by drugs such as imatinib.